The crystal structure of Ba2Mn(SeO3)2Cl2 containing 1∞[Mn(SeO3)2Cl2]4− chains - Geng Lei (Zeitschrift für Kristallographie - New Crystal Structures, 2021)
Ba2Mn(SeO3)2Cl2, orthorhombic, Pnnm (no. 58), a = 6.7685(5) Å, b = 12.8618(10) Å, c = 5.4685(4) Å, V = 476.06(6) Å3, Z = 2, Rgt(F) = 0.0191, wRref(F2) = 0.0854, T = 298(2) K.